Predictive Biomarkers for Bevacizumab in Anti-tumor Therapy - Qingqing PAN; Mengzhao WANG (Chinese Journal of Lung Cancer, 2011)
Bevacizumab, the monoclonal antibody of vascular endothelial growth factor (VEGF) has been applied to the therapy of several neoplasms, but an appropriate biomarker to predict the efficacy has not been found. Those markers can originate from peripheral circulation, tumor tissue and genes. Some researches have found that low level of vascular cell adhesion molecule-1 (VCAM-1), E-selectin, angiopoietin 2 (Ang-2) in circulation or carbonic anhydrase 9 (CA9), CD31-microvessel density (CD31-MVD) in tumor tissue can predict better activity of bevacizumab. Moreover, high level of soluble VEGFR2 (sVEGFR2) in circulation or the ratio of phosphorylated-VEGFR2 (p-VEGFR2) and VEGFR2 in tumor tissue increasing has the same predictive function. As to the gene, VEGF-634 CC, VEGF-1498 TT and VEGFR2 H472Q are only related to the side effct. Thus more clinical tirals and basic researches should be performed to find out effective biomarkers in bevacizumab’s therapy.